Penerapan Software Akuntansi SI APIK Pada UMKM Dapur Lisma - S, Suharyono (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
MSMEs play a strategic role in supporting the national economy, yet many business owners still do not prepare systematic financial statements. One such enterprise is Dapur Lisma, a home-based culinary business located in Bagan Melibur Village, Kepulauan Meranti, which had no formal financial recording or use of accounting software. This study aims to implement the SI APIK accounting application at Dapur Lisma and analyze its impact on financial reporting practices. The method used is a case study with a qualitative descriptive approach. Data were collected through observation, interviews, and documentation from March to November 2024. The results indicate that after implementing SI APIK, Dapur Lisma began recording daily transactions, separating personal and business finances, and producing basic financial reports. The application helped improve the owner's understanding of cash flow, costs, and net income, although further assistance is needed in account classification and transaction documentation. The study recommends simplification of the application features to be more user-friendly for beginner MSMEs.